Knowledge and belief: their role in science and communication. - Е. Е. Lednikov (Тонкие химические технологии)
In the paper in accordance with philosophical tradition to discern notions of knowledge and belief specific traits of contexts using these notions are exposed. Perspectives of construction rational theory of discussion about believes are evaluated.